"Where Is the Women's Center Here?": The Role of Information in Refugee Women's Help Seeking for Intimate Partner Violence in a Resettlement Context. (October 2021) - Wachter, Karin; Cook Heffron, Laurie; Dalpe, Jessica; Spitz, Alison
A qualitative study examined factors that hinder help seeking for intimate partner violence among women who resettled to the United States as refugees. A refugee resettlement agency recruited female clients ( n = 35) and service providers and stakeholders ( n = 53) in the metropolitan area. The study employed individual interviews and focus group discussions to collect data. An inductive and interpretive thematic approach guided the analytical process. The analysis revealed challenges related to information gaps and communication struggles complicating help-seeking processes. The findings point to the importance of bolstering information sharing within and across informal and formal networks to help women navigate support and services in resettlement.